2020
DOI: 10.1002/adfm.202007417
|View full text |Cite
|
Sign up to set email alerts
|

CO2‐Based Dual‐Tone Resists for Electron Beam Lithography

Abstract: The increasing global environmental and energy crisis has urgently motivated the advancement of sustainable materials. Significant effort has been focused on developing new materials to replace the fossil‐based resists in the semiconductor industry based on greener sources such as ice, dry ice, small organic molecules, and proteins. Such resist materials, however, have yet to meet the stringent requirements of high sensitivity, high resolution, reliable repeatability, and good compatibility with the current pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…We first studied the sensitivity of the present resist composition (NMeBTA) at different beam energies (Figure S15a). To advance our study on these resist compositions for their utilization in e-beam lithography (EBL), a film of NMeBTA was spin-coated on a 2 × 2 cm 2 silicon wafer from its PGMEA solution, which was then exposed initially with e-beam (kinetic energy of e-beam was 10 keV). The corresponding dose array indicating the energy on each square has been shown in Figure S15b.…”
Section: Resultsmentioning
confidence: 99%
“…We first studied the sensitivity of the present resist composition (NMeBTA) at different beam energies (Figure S15a). To advance our study on these resist compositions for their utilization in e-beam lithography (EBL), a film of NMeBTA was spin-coated on a 2 × 2 cm 2 silicon wafer from its PGMEA solution, which was then exposed initially with e-beam (kinetic energy of e-beam was 10 keV). The corresponding dose array indicating the energy on each square has been shown in Figure S15b.…”
Section: Resultsmentioning
confidence: 99%
“…Due to easy and complete degradation under diverse stimuli, polysulfones can be used as sensitive positive resists for electron beam lithography, which have similar behaviors to CO 2 -based polycarbonates. 117 Bowden and Thompson found that polysulfones derived from different terminal olefins have similar degradation rates, 118 and the sensitivity was of the order of 1–2 × 10 −6 coulomb per cm 2 at 5 kV, determined in solution development. Interestingly, it was reported that polysulfones could also be etched in a vapor development process.…”
Section: Copolymerization Of So2 and Olefinsmentioning
confidence: 99%
“…116 Due to easy and complete degradation under diverse stimuli, polysulfones can be used as sensitive positive resists for electron beam lithography, which have similar behaviors to CO 2 -based polycarbonates. 117 Bowden and Thompson found that polysulfones derived from different terminal olefins have…”
Section: Properties and Applicationsmentioning
confidence: 99%
“…We believe that a large pool of catalysts that exhibit diverse built-in reactivity will become accessible as their synthesis involves only the simple joining of amines, halohydrocarbons, and boranes; as a bonus, these components are generally commercially available on a large scale. The development of metal-residue-sensitive applications, such as elastomers, membranes, and lithography, will be promoted, benefiting from the continuous research on highly active metal-free boron catalysts. This Account should stimulate research on areas of other chemical conversions that are based mainly on the application of nucleophiles and electrophiles or Lewis acids and bases.…”
Section: Conclusion and Outlookmentioning
confidence: 99%